Vitamin D Supplementation Modulates Platelet-Mediated Inflammation in Subjects With Type 2 Diabetes: A Randomized, Double-Blind, Placebo-Controlled Trial - Johny, Ebin; Jala, Aishwarya; Nath, Bishamber; Alam, Md Jahangir; Kuladhipati, Indra; Das, Rupam; Borkar, Roshan M.; Adela, Ramu (Frontiers in Immunology, 2022)
Background Recently, our group identified increased platelet-mediated inflammation in type 2 diabetes (T2DM) patients, and it is a well-established risk factor for diabetes complications, particularly for the development of cardiovascular diseases (CVD). Furthermore, vitamin D is reported to play an important role in the modulation of platelet hyperactivity and immune function, although the effect of vitamin D on platelet-mediated inflammation is not well studied. Hence, we aimed to investigate the effect of vitamin D supplementation on platelet-mediated inflammation in T2DM patients. Methods After screening a total of 201 subjects, our randomized, double-blind, placebo-controlled trial included 59 vitamin-D-deficient T2DM subjects, and the participants were randomly assigned to placebo (n = 29) or vitamin D3 (n = 30) for 6 months. Serum vitamin D metabolite levels, immunome profiling, platelet activation, and platelet–immune cell aggregate formation were measured at baseline and at the end of the study. Similarly, the serum levels of inflammatory cytokines/chemokines were assessed by a multiplex assay. Results Six months of vitamin D supplementation increases the serum vitamin D3 and total 25(OH)D levels from the baseline (p < 0.05). Vitamin D supplementation does not improve glycemic control, and no significant difference was observed in immune cells. However, platelet activation and platelet immune cell aggregates were altered after the vitamin D intervention (p < 0.05). Moreover, vitamin D reduces the serum levels of IL-18, TNF-α, IFN-γ, CXCL-10, CXCL-12, CCL-2, CCL-5, CCL-11, and PF-4 levels compared to the baseline levels (p < 0.05). Our ex vivo experiment confirms that a sufficient circulating level of vitamin D reduces platelet activation and platelet intracellular reactive oxygen species. Conclusion Our study results provide evidence that vitamin D supportive therapy may help to reduce or prevent the disease progression and cardiovascular risk in T2DM patients by suppressing oxidative stress and platelet-mediated inflammation. Clinical Trial Registration Clinical Trial Registry of India: CTRI/2019/01/016921.